Membrane-bound NAC transcription factors in maize and their contribution to the oxidative stress response. (September 2016) - Wang, Dexin; Yu, Yanchong; Liu, Zhenhua; Li, Shuo; Wang, Zeli; Xiang, Fengning
Highlights: The seven ZmNTLs evolved together with other NAC members. Most of the ZmNTLs were strongly transcribed in response to abiotic stress exposure. The stress-induced transcription of ZmNTLs varied from organ to organ. Three of ZmNTLs contributed to the plant's defense against oxidative stress. Abstract: NAC membrane-bound transcription factors (NTM1-like, NTL proteins) participate in the regulation of plant development and the abiotic stress response. While their function has been thoroughly explored in Arabidopsis thaliana, this is not the case in maize. Seven ZmNTL genes were identified by an in silico scan of relevant genome sequence. All seven included a NAC domain at their N terminus, and an α-helical membrane-bound structure domain in their C terminal region. Based on their gene structure and content of conserved motifs, the seven sequences were distributed into four clades. Six of the seven ZmNTLs were associated with the plasma membrane, and the remaining one with the endoplasmic reticulum. ZmNTL2-7 were more strongly transcribed in the stem than in either the leaf or root, while ZmNTL1 transcript abundance was highest in the leaf. When the plants were exposed to either abscisic acid or hydrogen peroxide treatment, all seven genes were up-regulated in the root and stem and down-regulated in the leaf. The heterologous expression of ZmNTL1-ΔTM, 2-ΔTM and 5-ΔTM in A. thaliana reduced the level of sensitivity of the plant to hydrogen peroxide.